Body Mass Index, Eating Habits and Physical Activities of College Students at Catanduanes State University Panganiban Campus - Salvador, Rowel (JPAIR Multidisciplinary Research, 2024)
The transition from high school to university is a critical phase when students struggle to make healthy eating choices with adequate nutrition, affecting their academic status. This descriptive-correlational research investigated the body mass index, eating habits, and physical activities of one hundred twenty-four (124) Bachelor of Elementary Education college students at Catanduanes State University, Panganiban Campus, Catanduanes, Philippines. The researcher used the mean frequency to tabulate the result of the student’s socio-demographic profile, physical activities, and eating habits and the Pearson chi-square to determine the relationship of the variables. Analyzed data on sex revealed that the majority or 50.80% of the respondents have normal BMI, only 3 or 2.42% are obese; year level, majority or 29.03% are first year while 0.80% or 1 is irregular; family income is below Php 9,520; physical activities, majority or 54.83% “rarely” exercise while only 0.81% does it “usually”; eating habits, the respondents “seldom” skip meals aside from majority “seldom” eat the aforementioned list of foods by mealtime. No correlations were established between sex, physical activities, and BMI only along variable-eating habits (Pearson chi-square 14.484, p= 0.025). Thus, healthy eating habits constitute improved food knowledge and education, meal planning, participation in food preparation, and exercise, which reinforces a higher level of physical fitness associated with an increase in academic achievement.